Las estrategias educomunicativas como mecanismos para la divulgación científica de las condiciones eco-epidemiológicas de la plaga caracol gigante africano (L. fulica) en el Valle del Cauca - Zamudio Tobar, Gladys; Tamayo Montoya, Paula Andrea; Meneses Urrea, Luz Adriana; García Serna, Lyda Ruth; Cano Quintero, María Constanza; Cruz Mosquera, Freiser Eceomo (Universidad Santiago de Cali, 2025)
The objective three of the project “Eco-epidemiological investigation of the pest Giant African Snail (L. fulica) and its potential impact on the environmental health of Valle del Cauca”, led by the Universidad Santiago de Cali and executed with the collaboration of the Universidad del Valle, is to improve scientific dissemination on the eco-epidemiological conditions of this pest in the region. This chapter presents the educational-communication strategies designed for this purpose. The development of educommunicative strategies began with the formation of a multidisciplinary team of experts in education, psychology, public health and epidemiology. A qualitative participatory action research was used, organizing expectation, sensitization and dissemination workshops in five municipalities of Valle del Cauca: Cali, Caicedonia, Cartago, Buga and Buenaventura. Narrative techniques were used to interpret the qualitative data. Eight educommunicative strategies were created, including expert panels, workshops, video production, brochures, a scientific event and participation in mass media. These activities reached 1820 people from academic, business, government and civil society sectors. The educommunicative strategies are based on participatively generated information, promoting a significant awareness of the Giant African Snail problem. They encourage the appropriation of scientific knowledge, identify relevant territorial particularities, strengthen intersectoral collaboration and organize the community for the management of the pest, promoting a coexistence that minimizes its impact on biodiversity.